Analisis Potensi Ekowisata Dan Kesiapan Masyarakat Kecamatan Talamau Dalam Pengembangan Ekowisata - Agus, Ahmad Rasyid Ridho (JURNAL DESTINASI PARIWISATA, 2022)
Ecotourism is travel to natural areas that are not disturbed and contaminated with the specifications of objects of education, admiration, beauty of wild plants and animals, past and present culture. Talamau District has a lot of tourism potential both natural tourism and cultural tourism. These natural and cultural tourism potentials are very suitable to be developed into ecotourism which can increase the income of local people. . This study aims to determine the ecotourism potentials that exist in the Talamau District and the community's readiness to carry out ecotourism. This research is qualitative research with data collection techniques derived from interviews, observation, and literature study. Based on the data obtained, it is known that the tourism potential in the Talamau sub-district consists of natural and cultural potential, namely Mount Talamau, hot springs, Sarasah waterfalls, the traditional village of Talamau village, Malopeh Kaua and Rejecting Bala rituals, and the tradition of Manajalg Talu shoots. Based on the analysis conducted by researchers with the international ecotourism standard, it can be concluded that Talamau District is ready to develop ecotourism. Keyword: Ecotourism, Talamau, Potentials, Community Readiness